Determining the Sexual and Reproductive Health Needs of Deaf People in Ghana - Mprah Kwadwo Wisdom (Indonesian Journal of Disability Studies, 2015)
This article examines how deaf people in Ghana prioritize their sexual and reproductive health (SRH) needs. The aim is to determine the most pressing SRH needs of the deaf community in Ghana and then propose appropriate measures to make SRH information and services accessible to them. The study was a SRH needs assessment with deaf people in Ghana, which utilized a participatory needs assessment method. A total sample of 179 participants took part in the study: 26 were focus group participants, 152 were survey respondents, and one person acted as a key informant. The study findings indicated that deaf people in Ghana have many SRH challenges, but the most pressing needs were related to barriers associated with communication and attitude of health professionals. To design SRH programmes that are deaf-friendly, there is the need to take into account the linguistic and cultural values of the deaf community.